ARGON LOSS DURING DEFORMATION OF MICAS: CONSTRAINTS FROM LABORATORY DEFORMATION EXPERIMENTS - Dunlap W.J.; Kronenberg A.K. (My University, 2001)
The role of internal deformation in resetting argon ages of micas has been investigated by measuring 40Ar/39Ar ratios of biotite and muscovite, before and after experimentally deforming them. Neither mica crushed cataclastically at room temperature on-line with a mass spectrometer showed any measurable change in 40Ar/39Ar age. Muscovite crystals either sheared along the K-interlayer and/or kinked at 400°C and 100–200MPa confining pressure, exhibit small (0.7–1.0%) reductions in age and marked increases in bulk diffusion coefficients, as determined from argon release during the initial stages of step-heating between 550 and 810°C. We conclude that the relatively young ages of fine-grained mica populations in naturally deformed mylonites result primarily from grain size refinement and reductions in length scale for volume diffusion and/or by syntectonic neocrystallization. Internal deformation involving dislocation slip and kinking may contribute to some argon loss by pipe diffusion, but reductions in closure temperature associated with multipath diffusion are small.